Exploring long-term psychological effects of bronchiolitis and influenza in school-aged children - Soni, Pankaj; Cheriathu, Jenny (Frontiers in Pediatrics, 2025)
IntroductionThis systematic review assessed the long-term psychological effects of severe respiratory infections—namely, bronchiolitis and influenza—in school-aged children (5–12 years).MethodsPubMed, EMBASE, and the Cochrane Library were searched for randomized controlled trials, cohort and longitudinal studies on school-aged children (5–12 years) with a history of bronchiolitis or influenza infection in early childhood published between 2014 and 2022. Studies evaluating long-term psychological outcomes at least 6 months post-infection were included.ResultsSeveral studies that were included in this review reported increased risks of anxiety disorders, depression, and attention deficit among those with severe respiratory infections in early childhood. Additionally, studies with prolonged follow-up periods often reported a higher incidence of psychological morbidity in children. However, some studies did not detect significant long-term adverse effects, implying that timely interventions and supportive care may minimize negative psychological outcomes. This review underscores the necessity of mental health support following respiratory infections in children, highlights the need for further research on the biological and psychosocial pathways linking respiratory illnesses to psychological outcomes, and emphasizes the value of multidisciplinary treatment strategies for children with such comorbidities.ConclusionsThe findings of this review provide insights for healthcare practitioners, policymakers, and researchers to consider strategies aimed at improving the outcomes of respiratory illnesses in affected children.